A balancing act – Therapists’ experiences of conducting psychotherapy with psychosis clients - Knutsson, Jens; Jägestedt, Rebecka; Persson, Malin; Ramner, Jonas; Hoff, Eva (European Journal for Qualitative Research in Psychotherapy, 2023)
This study aimed to explore therapists’ experiences of providing therapy for people with a history of psychosis and examine the role played by psychotic symptoms in therapy. Interviews with 10 therapists were conducted and analyzed thematically using Interpretative Phenomenological Analysis. In the first of four themes, the therapists described a highly challenging work situation in which they first patiently needed to “unlock” their clients to lay the groundwork for an alliance. The second theme concerned the challenges of therapy for instance that, over the course of long-lasting therapies and under a recurring risk of psychotic contagion, therapists might temporarily lose their professionality, sometimes intentionally setting aside reality testing to assist their clients. The third theme encompassed the fine balance the therapists had to strike between strategies of supporting, to create safety, and confrontation, to aid progress in therapy. In the last theme, the therapists reported how using self-compassion and supervision as well as planning for recovery were crucial to cope with the turbulent process. Still, the therapists saw these therapies as interesting and remained fascinated by their clients, something that made their work highly rewarding. This knowledge about therapists’ experiences can be used to inform students in training and to develop therapeutic work with this client group.